O Design Instrucional no contexto da Arquitetura da Informação: contribuições em ambientes informacionais digitais inclusivos para a pessoa idosa - Goulart, Janaína Dias (Universidade Federal de São Carlos, 2023)
The increase in the world's elderly population reinforces the need to create inclusive information systems for this public. The objective of the research is to analyze the Instructional Design methodologies that can facilitate the inclusion of elderly people in digital informational environments with the help of Information Architecture. Information Architecture is related to different aspects of construction, storage, retrieval, and usability of informational environments. Instructional Design can be defined as a work methodology dedicated to the processes of analysis, design, development, implementation, and evaluation of distance courses that must be considered from the moment of conception of the training offer until its implementation. From these two definitions, it is possible to verify that the Information Architecture offers a theoretical basis, structuring the line of action of the professionals responsible for the design of the informational environment aimed at the elderly, indicating the best paths that will lead to the choice of the most suitable tools and resources. appropriate to the digital context that will be developed. Therefore, the research's guiding question was formulated: How can Instructional Design combined with Information Architecture contribute to the inclusion of the elderly in digital informational environments? The research is of a qualitative and quantitative nature, in which bibliographic, descriptive, and field research methodologies were used, using a questionnaire and direct observation as data collection instruments (applied to elderly people who attend courses in Informatics at FESC, a public institution from the city of São Carlos-SP) and interviews with professors of the same courses. The analysis of the results was carried out through content analysis. The main authors present in the theoretical framework of the research are Beauvoir, Haddad, Quintana, Alves Júnior, Casamayou and Gonzalez (aging process); Saracevic, Rosenfeld, Morville, Arango, Jorente, Vidotti, Vechiato and Oliveira referring to Information Architecture; Barreiro, Filatro and Piconez related to Instructional Design. The motivation for the research came from the author's experience with the elderly public as a teacher of Informatics courses and as an instructional designer. Bibliographical research and analysis of responses from interviews and questionnaires prove the need to create more inclusive digital informational environments to meet the needs of the elderly public who want to feel safe and autonomous in the digital context. It is hoped that these studies will bring new concepts of improved environments, which can be useful especially for the elderly and that it will bring more equity and make digital informational environments truly democratic and participatory for all audiences.
Instructional Design in the context of Informational Architecture: contributions in inclusive digital environments for the elderly
Keywords: Arquitetura da informação; Design Instrucional; Pessoa Idosa; Ambiente informacional digital; Acessibilidade; Information architecture; Instructional Project; Elderly; Digital informational environment; Accessibility; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::TEORIA DA INFORMACAO; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO